Penggunaan pendekatan contextual teaching and learning untuk meningkatkan kemampuan pemecahan masalah matematis siswa SMP kelas VIII pada materi teorema pythagoras - Ramaditya, Annisa Putri; Rosyana, Tina; Afrilianto, M. (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2024)
This study aims to study and analyze the improvement of mathematical problem-solving skills in students who use the Contextual Teaching and Learning approach. This research is a type of quasi-experimental research with the population of grade VIII students at SMP Negeri 2 Batujajar and the sample of this study is students of grades VIII B and VIII C. The data collection instrument in this study uses mathematical problem-solving ability test questions in the form of descriptions of five questions. Quantitative data processing used the analysis of 2 dependent samples with a normality test and continued with a paired t-test. The results of this study are: Improvement of mathematical problem-solving ability of junior high school students in grade VIII whose learning uses the Contextual Teaching and Learning approach is better than those who use ordinary learning in Pythagorean Theorem material because in their learning they use all the characteristics of CTL, so that they can train students to solve a problem presented.